Effect of whey on solid state fermentation of coffee (Coffea arabica L.) pulp for feeding ruminants - Aguirre, L. A.; Rodríguez, Zoraya; Bocourt, R.; Saca, V.; Salazar, R.; Jiménez, M. (Cuban Journal of Agricultural Science, 2018)
In order to evaluate the effect of the inclusion of different levels of whey in the solid state fermentation of coffee pulp, an experiment was carried out using a completely randomized design with a 4 x 4 factorial arrangement, with three repetitions. Factor A corresponded to whey levels (0, 5, 10 and 15 %) and B, to fermentation time (0, 24, 48 and 72 hours). The fermentation was carried out in Erlenmeyer of 1000 mL, and each flask constituted an experimental unit. The fermentative indicators (pH and NH3) were measured and the bromatological analysis was carried out: dry matter, ashes, crude protein, crude fiber, true protein, neutral detergent fiber and cellular content. The results showed interaction among the factors under study for the content of NH3, dry matter, crude protein, crude fiber, neutral detergent fiber and cellular content. There was no interaction for pH, true protein and ashes. The high content of crude protein (28.2 %, P<0.001), true protein (17.21 %, P<0.001) and crude protein / true protein relation (64.7 %, P<0.001) was obtained in the treatment with 10 % of whey until 48 h of fermentation. It is concluded that the inclusion of 10 % of whey in the solid state fermentation of coffee pulp up to 48 h improves the fermentation process, with marked increase of crude protein, true protein, and CP/TP relation. Although fiber components remain high, the use of whey in the preparation of rations for feeding ruminants could be encouraged. Keywords: agricultural residues, fermentative indicators, nutrients